Asian Americans and Pacific Islanders' perspectives on participating in the CARE recruitment research registry for Alzheimer's disease and related dementias, aging, and caregiving research. Issue 1 (19th July 2021) - Ta Park, Van; Grill, Joshua D.; Zhu, Jeanette; Nguyen, Khue; Nam, Bora; Tsoh, Janice; Kanaya, Alka; Vuong, Quyen; Bang, Joon; Nguyen, Nhi Cristina Y.; Cho, In Hyang; Gallagher‐Thompson, Dolores; et al.
Abstract: Introduction: This study elicited Asian Americans and Pacific Islanders' (AAPI) perspectives about recruitment strategies/messaging for participation in an aging, Alzheimer's disease and related dementias (ADRD), and caregiving research recruitment registry. Methods: Using a mixed methods design, CARE (Collaborative Approach for AAPI Research and Education) conducted 14 focus groups (N = 123) with AAPI cultural groups (Asian Indian, Chinese, Filipino, Japanese, Korean, Samoan, Vietnamese) in different languages. Descriptive statistics and thematic qualitative analyses were conducted. Results: Mean age of participants was 54 years (median: 61; range 18–80), 66% were female, and 81% were foreign‐born. Themes of consideration for recruitment emerged: (1) culturally/linguistically appropriate outreach in culturally specific spaces, (2) motivations for research participation, and (3) approaches to outreach and recruitment methods. Within each of these themes, there were ethnic differences in specific strategies/approaches reflected as subthemes. Discussion: Recruitment and messaging strategies should be tailored uniquely for each targeted AAPI group, with a thorough understanding of the cultural/linguistic factors that facilitate research participation to increase AAPI participation in ADRD, aging, and caregiver‐related research.